New insights into electrocatalytic ozone generation via splitting of water over PbO2 electrode: A DFT study - Gregory Gibson; Ashley Morgan; Peijun Hu; Wen-Feng Lin (2016)
© 2016 Elsevier B.V. All rights reserved. The viable mechanisms for O3 generation via the electrocatalytic splitting of H2O over β-PbO2 catalyst were identified through Density Functional Theory calculations. H2O adsorbed onto the surface was oxidized to form OH then O; the latter reacted with a surface bridging O to form O2 which in turn reacted with another surface O to form O3. The final step of the mechanisms occurs via an Eley-Rideal style interaction where surface O2 desorbs and then attacks the surface bridging oxygen, forming O3. A different reaction pathway via an O3H intermediate was found less favoured both thermodynamically and kinetically.